A Method for Reducing Grounding Impedance. Issue 1 (20th June 2013) - Ametani, Akihiro; Fujita, Yuta; Morii, Hiroshi; Kubo, Takashi
Summary This paper investigates grounding impedance reduction with various shapes of grounding electrodes in comparison with a conventional vertical rod based on field measurements and FDTD simulations. It is found that a vertical rectangular conducting plate is effective for reducing the transient and steady‐state impedance to less than half that of the vertical rod. A circular conducting plate parallel to the earth surface is also effective in reducing the steady‐state impedance, but the transient impedance is nearly the same as that of the vertical rod. The rate of reduction is proportional in some way to the surface area of the electrode, but tends to saturate as the area increases. The transient impedance is rather independent of the earth resistivity and permittivity, but tends to be inversely proportional to the wavefront duration of the applied current. © 2013 Wiley Periodicals, Inc. Electr Eng Jpn, 185(1): 27–35, 2013; Published online in Wiley Online Library (wileyonlinelibrary.com). DOI 10.1002/eej.22405